PPAR𝜸 and Oxidative Stress: Con(𝜷) Catenating NRF2 and FOXO - Simone Polvani; Mirko Tarocchi; Andrea Galli (PPAR Research)
Peroxisome-proliferator activator receptor γ (PPARγ) is a nuclear receptor of central importance in energy homeostasis and inflammation. Recent experimental pieces of evidence demonstrate that PPARγ is implicated in the oxidative stress response, an imbalance between antithetic prooxidation and antioxidation forces that may lead the cell to apoptotic or necrotic death. In this delicate and intricate game of equilibrium, PPARγ stands out as a central player devoted to the quenching and containment of the damage and to foster cell survival. However, PPARγ does not act alone: indeed the nuclear receptor is at the point of interconnection of various pathways, such as the nuclear factor erythroid 2-related factor 2 (NRF2), Wnt/β-catenin, and forkhead box proteins O (FOXO) pathways. Here we reviewed the role of PPARγ in response to oxidative stress and its interaction with other signaling pathways implicated in this process, an interaction that emerged as a potential new therapeutic target for several oxidative-related diseases.